Schistura albirostris, a new nemacheiline loach (Teleostei: Balitoridae) from the Irrawaddy River drainage of Yunnan Province, China - Chen, Xiao-Yong; Neely, David A. (Zootaxa, 2012)
Schistura albirostris, a new species of nemacheiline loach, is described from the Longchuanjiang, a tributary of theIrrawaddy River of Tengchong County, southwestern Yunnan, China. It differs from all congeners in the combination ofan extremely slender body; a distinctive rectangular unpigmented area on the snout, ethmoid region and anterior rostralbarbels; 5–7 dark dorsal saddles that are confluent with 5–8 lateral bars; lacking a suborbital flap in males; and possessing an incomplete lateral line with 27–51 pores, and a weakly-developed processus dentiformis.